PENGARUH KEPEMIMPINAN DAN PROGRAM K3 (KESEHATAN DAN KESELAMATAN KERJA) TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. TELKOM AKSES STO JIMBARAN - Made Benny Yuda Asrama; I Wayan Mendra; Yenny Verawati (VALUES, 2021)
Employee productivity is very necessary in a company to achieve targets and to keep the company stable. Given the importance of employee productivity, the company needs a leader who can direct and develop the business in accordance with the power he has towards achieving company goals. Special attention also needs to be taken by the company in order to increase employee productivity. The provision of Occupational Safety and Health (K3) programs is very important, especially for employees who are directly related to the production sector so that employees can feel safe, comfortable, healthy and safe in doing their jobs. This study aims to determine and analyze the influence of leadership and Occupational Health and Safety (K3) programs on the work productivity of PT. Access Telkom STO Jimbaran. The number of samples in this study were 72 employees of the Technician at PT. Telkom Akses STO Jimbaran. The sampling technique used in this study is the census/saturated method (saturated sample). The data analysis technique used is multiple linear regression analysis. The results showed that the leadership and the Occupational Health and Safety (K3) program had a significant positive effect on the work productivity of PT. Telkom Akses STO Jimbaran. These results indicate that the leadership and Occupational Health and Safety (K3) programs are able to produce better employee productivity and this must always be maintained by PT. Telkom Akses STO Jimbaran.